Identification of the Functional Domains of Yeast Sorting Nexins Vps5p and Vps17p - Seaman, Matthew N.J. (The American Society for Cell Biology, 2002)
Sorting nexins (Snxs) are a recently discovered family of conserved hydrophilic cytoplasmic proteins that have been found associated with membranes of the endocytic system and that are implicated in the trafficking of many endosomal membrane proteins, including the epidermal growth factor receptor and transferrin receptor. Snx proteins are partly defined by the presence of a p40 phox homology domain that has recently been shown to bind phosphatidylinositol 3-phosphate. Most Snx proteins also contain a predicted coiled-coils domain in the carboxyl-terminal half of the protein and have been shown to form dimers with other members of the Snx family. The yeast sorting nexins Vps5p and Vps17p form a dimer and are also components of the retromer complex that mediates endosome-to-Golgi transport of the carboxypeptidase Y receptor Vps10p. To functionally define the different domains of the yeast sorting nexins Vps5p and Vps17p, we have generated various truncations to examine the role that the different domains of Vps5p/Vps17p play in their respective functions. Herein, we show that the C-terminal halves of Vps5p and Vps17p, which contain the coiled-coils domains, are necessary and sufficient for their interaction. We have also mapped the retromer assembly domain to the N-terminal half of Vps5p and found that binding of Vps5p by Vps17p synergizes the interaction between Vps5p and other retromer components. Additionally, we have examined which domain(s) of Vps5p is necessary for membrane association.